New Answers to Old Conundrums: What Antibodies, Exosomes and Inflammasomes Bring to the Conversation. Canadian National Transplant Research Program International Summit Report. Issue 2 (February 2018) - Dieudé, Mélanie; West, Lori J.; Muruve, Daniel A.; Gunaratman, Lakshman; Mohanakumar, Thalachallour; Zorn, Emmanuel; Cairo, Christopher W.; Freed, Darren H.; Schultz, Kirk R.; Fairchild, Robert L.; Hébert, Marie-Josée
Abstract : Abstract: Antibody-mediated injury is a major cause of allograft dysfunction and loss. Antibodies to ABH(O) blood group antigens are classic mediators of ABO-incompatible graft rejection, whereas donor-specific anti-HLA antibodies and, more recently, autoantibodies are appreciated as important contributors to allograft inflammation and dysfunction. In August 2016, the International Summit of the Canadian National Transplant Research Program focused on recent advances in the field of antibody-mediated rejection. Here, we describe work presented and discussed at the meeting, with a focus on 3 major themes: the importance of (1) natural antibodies and autoantibodies, (2) tissue injury–derived exosomes and autoimmunity, (3) inflammasome activation and innate immune responses in regulating allograft inflammation and dysfunction. Finally, we explore novel areas of therapeutic intervention that have recently emerged from these 3 major and overlapping fields of transplantation research. Abstract : A summary report on these cutting-edge topics, from basic to translational, that impact allograft outcomes as discussed at the recent Canadian National Transplant Research Program (CNTRP) International Summit.